Self-reported Symptoms of Anxiety Predict Positive Suicide Risk Screening in Adolescents Presenting to the Emergency Department. Issue 1 (14th September 2020) - Powell, Daniel S.; Lanzillo, Elizabeth C.; Jay, Samantha Y.; Tanenbaum, Mira; Bridge, Jeffrey A.; Wharff, Elizabeth A.; Ballard, Elizabeth; Pao, Maryland; Horowitz, Lisa M.
Abstract : Objective: The objective of this study was to assess whether patient-reported anxiety symptoms are associated with suicide risk in pediatric emergency department (ED) patients. An additional objective was to examine differences between patients presenting for medical/surgical or psychiatric complaints. Methods: Pediatric patients aged 10 to 21 years were recruited from 3 pediatric EDs. Participants completed self-report questionnaires assessing for suicidal ideation and behavior, in addition to questions of interest about recent feelings of unbearable anxiety and depression. Adjusted odds ratios were calculated to assess the relationship between endorsement of recent anxiety and screening positive for suicide risk. Results: Data were analyzed from 522 participants, including 344 presenting with medical/surgical chief complaints and 178 presenting with psychiatric complaints. Overall, 28.9% of participants screened positive for suicide risk, 29.9% endorsed recent feelings of anxiety, and 24.3% endorsed recent feelings of depression. Patients who self-reported recent anxiety symptoms were 5 times more likely to screen positive for suicide risk (adjusted odds ratios = 5.18, 95% confidence interval = 3.06–8.76). Analysis of the 344 medical/surgical patients revealed that this subsample was also 5 times more likely to screen positive for suicide risk if they endorsed recent anxiety (adjusted odds ratios = 4.87, 95% confidence interval = 2.09–11.36). Conclusions: Self-reported suicidal ideation and feelings of unbearable anxiety are prevalent among patients presenting to pediatric EDs. Patients who self-report recent feelings of unbearable anxiety are significantly more likely to screen positive for suicide risk, regardless of whether their presenting complaint is medical/surgical or psychiatric in nature.